Indonesian Political Party Website Portal Evaluation Rank based on Manual and Automated Usability Score - Abdillah, Rosyid; Riski, Raulia; Asfari, Ully (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
As Indonesia approaches a crucial election year in 2024, the digital engagement of political parties website plays a significant role in shaping the government's future direction. This study evaluates the usability of 17 official political party websites using both manual expert assessments and automated tools, providing insights and recommendations for improving their digital presence on basic layer of information. Based on the study of 17 political party websites in Indonesia, manual usability testing by experts showed an average agreement rate of 80%, with layout receiving the lowest score of 70%. Automated usability testing revealed that 5.9% of the websites received a grade B, 17.6% grade C, 41.2% grade D, 23.5% grade E, and 11.8% grade F, resulting in a comprehensive ranking from two different perspectives.